The effect of dietary Red Palm Oil on the functional recovery and the PKB/Akt pathway in the ischaemic/reperfused isolated rat heart - Odendaal, Louise (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.